2003
DOI: 10.1176/appi.ajp.160.7.1286
|View full text |Cite
|
Sign up to set email alerts
|

Insurance Expenditures on Bipolar Disorder: Clinical and Parity Implications

Abstract: Bipolar disorder is the most expensive behavioral health care diagnosis, both for patients with bipolar disorder and for their insurance plans. For every behavioral health care dollar spent on outpatient care for patients with bipolar disorder, $1.80 is spent on inpatient care, suggesting that better prevention management could decrease the financial burden of bipolar disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
78
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(79 citation statements)
references
References 12 publications
0
78
0
1
Order By: Relevance
“…Many extracellular receptors (such as 5-HT 2 , a 1 , M1, 3,5) are coupled to the G protein, G q/11 , which, through activation of phospholipase C (PLC), mediates the hydrolysis of a membrane phospholipid, phospholipase phosphoinositide 4,5-bisphosphate (PIP 2 ), to form the second messengers diacylglycerol (DAG) and inositol-1,4,5-triphosphate (IP 3 ) (see Gould and Manji 15 and Majerus 43 for review). DAG and IP 3 subsequently modulate the activity of a multitude of intracellular events (see greater discussion later in the phosphoinositol signaling section).…”
mentioning
confidence: 99%
“…Many extracellular receptors (such as 5-HT 2 , a 1 , M1, 3,5) are coupled to the G protein, G q/11 , which, through activation of phospholipase C (PLC), mediates the hydrolysis of a membrane phospholipid, phospholipase phosphoinositide 4,5-bisphosphate (PIP 2 ), to form the second messengers diacylglycerol (DAG) and inositol-1,4,5-triphosphate (IP 3 ) (see Gould and Manji 15 and Majerus 43 for review). DAG and IP 3 subsequently modulate the activity of a multitude of intracellular events (see greater discussion later in the phosphoinositol signaling section).…”
mentioning
confidence: 99%
“…One report from 2012 estimated that the per-patient cost for each inpatient stay ranged from $4356 to $7593 44 . Other research has found that 21% of patients with bipolar disorder are hospitalized in a given year 13 . The potential cost consequences of reducing hospitalizations for patients with bipolar disorder treated with antipsychotics by half on a population level could be substantial.…”
Section: Discussionmentioning
confidence: 98%
“…Bipolar disorder appears to be the most expensive psychiatric condition for commercial health plans in the US 11 , with hospital admissions comprising a large portion of the healthcare costs 12 . A study of commercial health insurance plan expenditures found that while only 3.0% of their beneficiaries had bipolar disorder, these patients accrued 12.4% of all behavioral health expenses driven by disproportionate use of inpatient care 13 . The importance of reducing hospitalizations has grown since the Centers for Medicare and Medicaid Service began to penalize hospitals for excessive readmission rates for certain conditions 14 , although psychiatric conditions are not currently included.…”
Section: Introductionmentioning
confidence: 99%
“…El TB puede ser motivo de incapacidad laboral absoluta, este hecho unido a los costosos gastos sanitarios que lleva asociados (Wyatt y Henter, 1995;Peele, Xu y Kupfe, 2003) provoca un grave impacto económico sobre su núcleo familiar (Reinares et al, 2006). Además de impedir la incorporación laboral del paciente, perjudica seriamente el desempeño laboral de los cuidadores, y muy especialmente el del cónyu-ge (Dore et al, 2001;Simon, 2002).…”
Section: Impacto Laboral Y Económico De La Enfermedadunclassified